Пряма регенерація мікропагонів з листкових дисків ківі (Actinidia delisiosa (Chev.) Liang, Ferguson) в умовах in vitro - Mitrofanova, I.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
The method of direct regeneration of microshoots from leaf disks of kiwi fruit is developed. The factors influencing morphogenetic potency of leaf disks of 4 kiwi fruit cultivars (Bruno, Monti, Tomuri, Sanishton) in condition in vitro are determined. The genetically uniform plant material is obtained.